1995
DOI: 10.1016/0014-2999(95)00066-t
|View full text |Cite
|
Sign up to set email alerts
|

YM-14673, a thyrotropin-releasing hormone analogue, injected into the nucleus accumbens and the striatum produces repetitive jaw movements in rats

Abstract: receptors may at least partly contribute to these effects. Anyhow, these mechanisms differ from that underlying the ability of YM-14673 and TRH to elicit wet-dog shakes, a mechanism that is known to involve serotonergic processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
(27 reference statements)
1
3
0
Order By: Relevance
“…Particularly relevant to the findings we report here are experiments suggesting that the behavioral patterns stimulated by increased intrastriatal TRH in intact non-primate mammals are akin to human dyskinesia [57], [58], [59], [60], [61], [62], [63]. Studies have suggested that the behavioral effects of TRH are exerted via the stimulation of striatal dopamine release [64], and that they can be antagonized by both D1-class and D2-class dopamine receptor antagonists [57], [58], [59].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Particularly relevant to the findings we report here are experiments suggesting that the behavioral patterns stimulated by increased intrastriatal TRH in intact non-primate mammals are akin to human dyskinesia [57], [58], [59], [60], [61], [62], [63]. Studies have suggested that the behavioral effects of TRH are exerted via the stimulation of striatal dopamine release [64], and that they can be antagonized by both D1-class and D2-class dopamine receptor antagonists [57], [58], [59].…”
Section: Discussionsupporting
confidence: 54%
“…Studies have suggested that the behavioral effects of TRH are exerted via the stimulation of striatal dopamine release [64], and that they can be antagonized by both D1-class and D2-class dopamine receptor antagonists [57], [58], [59]. In turn, striatal dopamine levels have also been shown to modulate the release of TRH within the rat striatum [61], [62], with higher levels of dopamine correlating with higher levels of intrastriatal TRH.…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effect maintained for as long as 8 h, which was in consistency with the long half-life of Taltirelin ( Kinoshita et al, 1998 ). Besides, animals exhibited involuntary shaking and repeated jaws action after the injection of Taltirelin above 5 mg/kg ( Supplementary video ), which may be related to the stimulation of 5-HT system ( Miwa et al, 1995 ) by Taltirelin during high dose use. We also examined and found that Taltirelin (>5 mg/kg) elevated serum level of TT3, TT4, FT3, and FT4 in PD rats (Supplementary Figure S5 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that the nucleus accumbens play a role in jaw movements elicited by YM-14673 (1). Since the response to YM-14673 was attenuated by the dopamine D1/D2 receptor antagonist cis-(Z)-flupentixol (1), it is suggested that YM-14673 directly or indirectly enhanced the dopamine activity at the level of dopamine D1/D2 receptors.…”
Section: Drugsmentioning
confidence: 99%